Evidence for a new geomagnetic jerk in 2014. Issue 19 (3rd October 2015) - Torta, J. Miquel; Pavón‐Carrasco, F. Javier; Marsal, Santiago; Finlay, Christopher C.
Abstract: The production of quasi‐definitive data at Ebre observatory has enabled us to detect a new geomagnetic jerk in early 2014. This has been confirmed by analyzing data at several observatories in the European‐African and Western Pacific‐Australian sectors in the classical fashion of looking for the characteristic V shape of the geomagnetic secular variation trend. A global model produced with the latest available satellite and observatory data supports these findings, giving a global perspective on both the jerk and a related secular acceleration pulse at the core‐mantle boundary. We conclude that the jerk was most visible in the Atlantic and European sectors. Key Points: Direct observations indicate a new geomagnetic jerk at 2014 A global perspective is given by a new model which confirms the jerk IGRF‐12 secular variation predictions might be poorer than expected